Serum metabolic profile analysis of syndrome of Qi-yin deficiency and Yang deficiency in diabetic coronary heart disease by UPLC-Q/TOF MS - Shenghua PIAO; Lei ZHANG; Ziqin ZHU; Huixia ZHAN; Xianglu RONG; Jiao GUO (KeAi Communications Co., Ltd., 2022)
Aims: Qi-yin deficiency (QYD) and Yang-deficiency (YD) syndrome are two common syndromes with contrasting clinical manifestations of low fever and cold phobia. Different syndrome phenotypes must have distinct biological underpinnings in vivo. Based on serum metabolomics, this study aims to reveal the biological characteristics of the two diabetic coronary heart disease syndromes mentioned above. Methods: A total of 33 diabetic coronary heart disease (DCHD) patients were included in the study, with 13 cases of QYD, 11 cases of YD syndrome, and 9 cases of Pinghe constitution (PH). Based on UPLC-Q/TOF MS, metabolomics was used to detect and analyze serum samples from the three groups mentioned above. To find differentiating metabolites, PLS-DA (Partial least squares discrimination analysis) and database searching were used. Meanwhile, the metabolic pathways of various metabolites were investigated. Results: There were 17 different metabolites between QYD syndrome and YD syndrome of DCHD. Cyclic GMP, LysoPE (20:3), proline, isoleucine, N-lactoyl-tyrosine, 3-oxohexadecanoyl-CoA, and oxalosuccinic acid were lower in the (YD) group than those in the PH group, while galactitol, N-lactoyl-tyrosine, and oxalosuccinic acid were higher in the QYD group than in the PH group. The 17 differential metabolites mentioned above were linked to a variety of pathways, including amino acid metabolism, purine metabolism, fatty acid elongation in mitochondria, the tricarboxylic acid cycle, lipid metabolism, energy metabolism, etc. Conclusion: Different DCHD syndromes, such as liver-kidney Yin deficiency and YD syndrome, have different biological bases for the same disease. To some extent, the findings of this study provide a scientific foundation for different approaches to treating the same disease in Traditional Chinese Medicine. It is also important for guiding the clinical use of herbal medicine.